2013
DOI: 10.1016/j.yexmp.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

High expression of the RNA-binding protein RBPMS2 in gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract and are often associated with KIT or PDGFRA gene mutations. GIST cells might arise from the interstitial cells of Cajal (ICCs) or from a mesenchymal precursor that is common to ICCs and smooth muscle cells (SMCs). Here, we analyzed the mRNA and protein expression of RNA-Binding Protein with Multiple Splicing-2 (RBPMS2), an early marker of gastrointestinal SMC precursors, in human GISTs (n=23) by in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
(27 reference statements)
0
31
1
Order By: Relevance
“…Previous studies demonstrated that post-transcriptional events control the development and the plasticity of different types of smooth muscles through miR or RNA-binding protein expression and function (2,3,7,8,9,11). Among these important players is the RNA-binding protein RBPMS2, which is involved in digestive SMC development and plasticity through the control of BMP signaling activity (9,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated that post-transcriptional events control the development and the plasticity of different types of smooth muscles through miR or RNA-binding protein expression and function (2,3,7,8,9,11). Among these important players is the RNA-binding protein RBPMS2, which is involved in digestive SMC development and plasticity through the control of BMP signaling activity (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Human RBPMS2 cDNA was used as template (11). The substitution of L49 by E or Q in human RBPMS2 was done with the QuikChange site-directed mutagenesis kit and protocol (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nuclear (Nuc), cytoplasmic (Cyt), and total cell lysate (Tot) fractions were resolved on a 4%-12% SDS-polyacrylamide gel and then probed using an anti-HA antibody targeting FLAG-HA RBPMS and RBPMS2, and antibodies targeting ELAVL1 (HuR), TUBB (β-tubulin), and LMNB1 (lamin B) as controls for the purity of the cytoplasmic and nuclear fractions. Dysregulation of RBPMS family proteins has been reported in cancer (Skawran et al 2008;Miller and Stamatoyannopoulos 2010;Drozdov et al 2012;Hapkova et al 2013; http://www.cbioportal.org/public-portal/) and chronic intestinal pseudo-obstruction (Notarnicola et al 2012). Manipulation of RBPMS levels during embryogenesis suggested functions in X. laevis oocyte maturation (Zearfoss et al 2003), heart and kidney development (Gerber et al 2002), and retinal ganglion cell development (Hornberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%